An MPC based active and reactive power coordinated control strategy of PMSG wind turbines to enhance the support capability - Ma, Xiyuan; Yu, Jingyi; Yang, Ping; Wang, Pengyu; Zhang, Peng (Frontiers in Energy Research, 2023)
As wind turbines are constantly replacing traditional units, it is becoming a consensus that wind turbines should participate in the grid support that was only responsible by traditional units in the past. In order to enhance the grid support capabilities (including active power support and reactive power support) of permanent magnet synchronous generator (PMSG) based wind turbines, this paper constructs an active and reactive power coordinated control strategy using model predictive control (MPC) technique. Compared with the current active and reactive power coordinated control strategy of PMSG wind turbines, the proposed one innovatively considers the climbing coordinated restriction between active and reactive power, flexible prioritization arrangement between active and reactive power, and the accurate amplitude and climbing constraints of grid-side converters’ output voltage. The simulation results verify that the proposed power control strategy can make PMSG wind turbines achieve excellent power output performance and thus better meet the requirements of power grid support.